(untitled) (Ius Novum, 2024)
The article is original in nature and was devoted to the problem of awards and prizes for e-sports players. The motivational financial instruments in question are regulated in the Law on Sports in Article 31. Within the framework of the study, the author attempted to solve the legal problem of finding an answer to the question of the legal possibility of establishing and financing awards and prizes for e-sports players by municipalities on the basis of Article 31 of the Law on Sports. Due to the unitary and causal works in the field of e-sports financing, however, which do not address the issue of establishing and financing awards and prizes for players of electronic sports on the basis of Article 31 of the Law on Sports, the development of this issue within the framework of the article, in the author’s opinion, will undoubtedly enrich the current literature on the subject. The preliminary considerations focus on presenting the essence of the definition of sports and an attempt to qualify e-sports as sports under the Law on Sports, which has important implications for the possibility of establishing prizes and awards by the local authorities. Relevant views of the literature, judicial decisions and the state of the law in this area were presented. Investigations in this regard led to the conclusion that it is possible to qualify e-sports as a sport under several reservations. Subsequently, the focus was on the legal aspects concerning the possibility of municipalities establishing and financing awards and prizes for e-sports players. The problem of understanding competition on the grounds of the Law on Sports was resolved, and it was pointed out that e-sports players, despite the lack of a Polish e-sports association, can participate in sports competition on the grounds of the Law on Sports. In addition, the understanding of the problematic in practice premise concerning the importance of a given sport for the local authority was clarified. Finally, considerations in this area allowed the formulation of postulates de lege ferenda. The subject of analysis are legal norms and statements of doctrine and jurisprudence. The article includes considerations of the normative and dogmatic sphere, as well as the sphere of application of law by administrative courts. The research is domestic in nature. This article uses the dogmatic-legal method of analyzing the legal regulations on the establishment and financing of prizes and awards of electronic sports players.